Village Governance Strategy to Mitigate Deforestation for Sustainability. - Rohmawati Kusumaningtias; Rediyanto Putra; Romi Ilham; Ayu Fitriatul Ulya; Bayu Rama Laksono (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction/Main Objectives: The study aims to establish a village governance strategy prioritising sustainability and community welfare. Background Problems: The problem of deforestation due to economic reasons is a fundamental reason that looks simple but involves many components. The economic sector impacts culture, macro policies and politics, and the most considerable influence is environmental sustainability. So, significant intervention is needed through appropriate governance, namely based on innovative forest business. Apart from that, the touch of ICT aligns with efforts to increase smart tourism. Novelty: Smart forest tourism that pays attention to sustainability and community welfare. Research Methods: This study utilises a phenomenological approach with the research location in Sambongrejo Village, Bojonegoro Regency, to identify deforestation problems. The study utilises SWOT analysis to determine the village governance strategy through external intervention and smart tourism. The research integrates intentional analysis by combining noema and noesis, followed by epoche to gather data on deforestation issues. Eidetic reduction is then used to distil the essence of consciousness, leading to proposed forest management strategies. These strategies, once implemented, hold the promise of a significantly more sustainable future for the village, confirming the forest management interpretation. Finding/Results: The SWOT analysis emphasises the internal and external factors from humans, nature, policies, and stakeholders that necessitate consideration for strategic steps to mitigate deforestation. Conclusion: The strategic efforts involve external intervention and the implementation of smart tourism, including the stages of smart destination, smart experience, and smart forest business, focusing on rights, incentives, and technology.